1992
DOI: 10.1136/adc.67.7_spec_no.793
|View full text |Cite
|
Sign up to set email alerts
|

Superior mesenteric artery blood flow velocity in necrotising enterocolitis.

Abstract: Doppler measurements of blood flow velocity were obtained from the superior mesenteric artery (SMA), coeliac axis, and anterior cerebral artery (ACA) of 19 infants with suspected necrotising enterocolitis, which was classified as confirmed (n=9) or unconfirmed (n=8). Infants with confirmed disease were compared with controls who were either enterally fed or who were receiving intravenous fluids.SMA velocity was significantly higher in the infants with confirmed necrotising enterocolitis (36.5 cm/s) than in unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 18 publications
(6 reference statements)
5
57
0
2
Order By: Relevance
“…We found no statistically significant difference in celiac artery blood-flow velocity indices between the 2 patient groups. Our findings agreed with an observation, made in the previous studies, that the risk of NEC was not associated with resistance in the celiac artery [15,23]. The origins of the CA and SMA from the Died from septic shock CA PI celiac artery pulsatility index, CA PSV celiac artery peak systolic velocity, CA EDV celiac artery end-diastolic velocity, CA RI celiac artery resistivity index, SMA PI superior mesenteric artery pulsatility index, SMA PSV superior mesenteric artery peak systolic velocity, SMA EDV superior mesenteric artery end-diastolic velocity, SMA RI superior mesenteric artery resistivity index, CA PSV/SMA PSV celiac artery peak systolic velocity/superior mesenteric artery peak systolic velocity descending aorta are almost contiguous, yet they supply very different vascular beds.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found no statistically significant difference in celiac artery blood-flow velocity indices between the 2 patient groups. Our findings agreed with an observation, made in the previous studies, that the risk of NEC was not associated with resistance in the celiac artery [15,23]. The origins of the CA and SMA from the Died from septic shock CA PI celiac artery pulsatility index, CA PSV celiac artery peak systolic velocity, CA EDV celiac artery end-diastolic velocity, CA RI celiac artery resistivity index, SMA PI superior mesenteric artery pulsatility index, SMA PSV superior mesenteric artery peak systolic velocity, SMA EDV superior mesenteric artery end-diastolic velocity, SMA RI superior mesenteric artery resistivity index, CA PSV/SMA PSV celiac artery peak systolic velocity/superior mesenteric artery peak systolic velocity descending aorta are almost contiguous, yet they supply very different vascular beds.…”
Section: Discussionsupporting
confidence: 93%
“…However, the lack of an increase in diastolic flow velocities and the increase in the RI constitute a very strong argument for splanchnic vascular constriction [24]. Our results agree with previous research that states that conditions, such as established neonatal necrotizing enterocolitis, are associated with increased superior mesenteric artery (SMA) blood-flow velocity [23,25]. Moreover, in an animal model of NEC, animals with severe NEC showed increases in PSV and RI values, which may suggest that profound bowel ischemia is a trigger for NEC in susceptible animals [24].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[1][2][3][4][5] Several reports have shown that enteral feeding induces a significant and progressive increase in blood flow velocity in the superior mesenteric artery that peaks 45-60 min after the meal. [6][7][8][9][10][11][12] The effect of feeding increases with the volume of milk and the interval between feedings. The increase in velocity peaks earlier after breast milk than after formula feeding.…”
Section: Introductionmentioning
confidence: 99%